Method of Pylorus-Preserving Duodenoplasty in Surgery of Performed Duodenal Ulcers - Izatillaev I. R.; Khozhimetov D. Sh. (Scholars Digest Publishing, 2023)
According to the World Health Organization, duodenal ulcer disease (DU) affects 10-15% of the world's population. Perforated duodenal ulcer (PDU) to this day continues to occupy a leading place in the structure of frequency (10-20%) and mortality (2.0-20%). At the same time, the results of surgical treatment are not completely satisfactory. Despite two centuries of experience in the treatment of DU, including its complications of perforation, it has made it possible to test and use all surgical interventions known in gastric surgery. At the same time, in many clinics the main emergency operation remains suturing, performed in 45-80% of patients. However, this surgical intervention is palliative and in 34-85% of cases requires reoperation.